Phytochemical and crystallographic studies of Azara dentata extracts and its cytotoxic effects on human breast cancer cell, MCF-7 - Paz, Cristian; González Chavarría, Iván; Freire Espeleta, Eleonora; Ortiz, Leandro; Karpiński, Tomasz M.; Duprat, Felix; Baggio, Ricardo Fortunato (Sociedad Chilena de Química, 2020)
Fil: Paz, Cristian. Universidad de La Frontera; Chile